Exergy analysis of evaporative cooling for reducing energy use in a Malaysian building - Taufiq, B.N.; Masjuki, Haji Hassan; Mahlia, T.M.I.; Amalina, M.A.; Faizul, M.S.; Saidur, Rahman (Desalination, 2007)
To reduce energy consumption in the buildings and minimize negative environmental impacts, it is necessary to determine the operating condition that provides optimum system performance. Entropy or exergy analysis can be used as a reliable tool for analyzing energy consumption and environmental impact. This paper describes the modelling and optimization analysis for cooling system in the building. Exergy technique has been used to evaluate overall and component efficiencies and to identify thermodynamic losses. The method is well suited for analyzing thermodynamic model and identified exergy losses of air conditioning application in a building.